Sosialisasi dan Lomba Kreativitas Daur Ulang Sampah di SMP Advent Tompaso Kabupaten Minahasa, Sulawesi Utara - Deviana Munthe; Sudarno P Tampubolon (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2024)
Abstract The concept of waste reduction (reduce), recycling or reusing (reuse/recycle), and safe disposal (dispose) is highly crucial in mitigating waste pollution today. The Community Service activity carried out at SMP Advent Tompaso through socialization and a creative waste recycling competition themed "Reduce Wasted and Save The Earth" underscores the importance of these principles. The enthusiasm of the students to learn about waste recycling methods in their environment, which can hold significant economic and market value, is evident. Furthermore, the participation of each class, sending their teams to compete in every contest, demonstrates their active involvement. From the two contests, namely the fashion show and waste recycling craft competition, it is apparent that each student possesses high levels of creativity. Plastic and paper waste transformed into clothing showcased in the fashion show highlight the variety of designs created. Meanwhile, the crafting of plastic waste into flower-shaped handicrafts demonstrates both economic and market value. Through the dissemination of information and the competitions, the hope is that students will not only become more environmentally conscious but also actively contribute to mitigating the impacts of global warming. They are encouraged not to dispose of waste recklessly but instead to start sorting waste in their surroundings, thus contributing to the preservation of the world and their immediate environment. Keywords: Socialization; creativity; trash, recycling, competition